NATO-SCO: STRUGGLE AGAINST TERRORISM AND/OR FOR DOMINATION IN CENTRAL ASIA - KHAMRAEV, Farkhad (CENTRAL ASIA AND THE CAUCASUS, 2002)
The cardinal changes of the early 1990s altered the geopolitical structure and the map of the world beyond recognition. The world is gradually becoming more interconnected and more vulnerable, as well as more complex and dynamic. Globalization has already destroyed the West-East and the North-South structures; the old thinking along the “friend or foe” line died while the new realities reject the approach that described the regions as the “center” and “periphery” or as of “primary” and “secondary” importance.The 9/11 events confirmed this paradigm, but anybody wishing to assess their impact on the international system should avoid extremes. The world is changing beyond recognition, yet new realities are rooted in the past while the old ones are not retreating without trace. The situation is very much complicated by this coexistence, which adds uncertainty to international relations, imposes moderation on all participants, calls for caution in political decision-making, and urges to take account of the current varied developments and the wealth of human history. The global political developments indicate that the great powers are resuming their Big Game in Central Asia; today they are driven by geo-eco-nomic (read: resources) rather than geopolitical factors as in the past. Considerable fuel reserves and development projects are turning the region into a nerve center of world politics. Central Asia, which has found itself at the frontline of struggle the world community is waging against international terrorism, religious extremism, drugs, and organized transborder crime, is gaining weight in the newly emerging system of international relations. The following describes the new geopolitical situation in a broad strategic context. First, the West’s active presence in the region as a logical consequence of the need to do away with the threat of international terrorism emanating from Afghanistan. Second, America’s long-term politics in the macro region of Central and South Asia prompted by U.S. national security interests in the 21st century. Third, as a result of the above processes and the considerably reduced threats presented by Afghanistan the region has acquired unique possibilities for integrated development and modernization with the international community’s active support. Since the very first days of independence the Central Asian countries have been building up a flexible and reliable regional security system to oppose external and internal threats and challenges. The process is slowed down by unresolved problems and contradictions. The first steps have been taken: the region is a nuclear-free zone; it should be said in this connection that the Shanghai Cooperation Organization (SCO) set up in June 2001 is gaining weight and influence as time goes on.